ANSWER
D. -3 and 4
EXPLANATION
The given quadratic trinomial is
![{x}^(2) + x - 12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cl47of7ll0kptf70kdxepm9ybhfmr1r1l7.png)
To factor this we need to find two factors of -12 that sum up to 1, the coefficient of x.
We can see from the table that, when p=-3 and q=4, then p+q =1.
The trinomial can now be factored as:
![{x}^(2) + x - 12 = (x - 3)(x + 4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2c1k0sb8ac4yv8q5hddumc87o8feaqv2hh.png)
The correct answer is D.